2017
DOI: 10.29040/jap.v18i01.80
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Komunikasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Badan Perencanaan Pembangunan Daerah Kabupaten Sukoharjo Dengan Motivasi Sebagai Variabel Intervening

Abstract: The purpose of this study was to test the significance of the influence of communication, work environment on employee performance Regional Planning Agency Sukoharjo with motivation as an intervening variable. The population in this study were employees of the Regional Development Planning Agency Sukoharjo. The sample in this study all employees. Data used in the study is primary data taken with a list of statements given to all employees. The analysis tools used are validity , reliability testing, linearity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Communication is a primary need that is not only in the form of verbal but also uses non-verbal forms, the relationship that exists both structurally and emotionally between people in a company is one of the factors supporting the effectiveness of achieving organizational goals. The results of this study are supported by several studies by Arianto, (2015); Sundari & Okfitasari, (2017); and Sumaki et al, (2015).…”
Section: Effect Of Communication On Employee Performancesupporting
confidence: 91%
See 1 more Smart Citation
“…Communication is a primary need that is not only in the form of verbal but also uses non-verbal forms, the relationship that exists both structurally and emotionally between people in a company is one of the factors supporting the effectiveness of achieving organizational goals. The results of this study are supported by several studies by Arianto, (2015); Sundari & Okfitasari, (2017); and Sumaki et al, (2015).…”
Section: Effect Of Communication On Employee Performancesupporting
confidence: 91%
“…Communication can be interpreted as a process of transferring information, ideas, understanding from one person to another in the hope that the other person can interpret it according to the intended purpose (Mangkunegara, 2015;Soeradi et al, 2023). Research conducted by Arianto, (2015); Sundari & Okfitasari, (2017);and Sumaki et al, (2015) showed the result that communication has a positive and significant effect on employee performance. Thus, the better the relationship between leaders and employees and employees with other employees, the better the performance.…”
Section: Introductionmentioning
confidence: 99%
“…Motivation is important because with this motivation it is hoped that every examiner will work hard and be enthusiastic to achieve high work productivity.Motivation is closely related to the performance of the examiner, so with the motivation of employee performance is increasing. Organizational management in determining the disciplinary standards of the examiner will greatly affect the motivation of the examiner.Previous research has found that there is an influence between work discipline and work motivation (Sundari & Oktafianti, 2017, Rosento et al 2019). H6:…”
Section: Introductionmentioning
confidence: 96%
“…Employees have an important role in a company, namely as thinkers, planners and those who control company activities. By remembering the important role of HR in the company, employee performance determines the success or achievements of the company itself (Fudzah et al, 2020). Compensation and organizational culture are part of the feedback relationship between the organization and HR.…”
Section: Introductionmentioning
confidence: 99%
“…An employee is declared to have good performance if the employee himself is able to provide work results that are the same or exceed the standards or characteristics that have been determined jointly in a company or organization. Meanwhile, on the contrary, employees are declared to have no performance if their work results are less than the standards or criteria that have been determined together (Fudzah et al, 2020). (Yuniyanto et al, 2023) Compensation is a reciprocity given to customers for services to carry out the duties, obligations and responsibilities assigned to them with the aim of achieving organizational goals.…”
Section: Introductionmentioning
confidence: 99%